The Effect of Bullying on Depression, Academic Activity, and Communication in Adolescents in Surakarta: A Multilevel Logistic Regression - Kiyat Sudrajad; RB Soemanto; Hanung Prasetya (Journal of Health Promotion and Behavior, 2020)
Background: Human interaction requires communication as a transmission of information, ideas, emotions, skills, and so on. Communication occurs when a source conveys a message to the recipient with a conscious intention to influence the recipient's behavior. One of the problems in social communication is bullying. Bullying or harassment can be through words or through actions that aim to make the opponent's mental fall and pressure. The purpose of this study was to analyze the factors that influence bullying against depression with the Health Belief Model and Social Cognitive Theory.Subjects and Method: This was a cross-sectional study conducted in junior high schools in Surakarta, in December 2019. A total sample of 250 adolescents was selected by simple random sampling. The dependent variable was bullying. The independent variables were perceived susceptibility, perceived severity, cues to action, perceived threat, perceived benefit, perceived barrier, self-efficacy, depression, academic activities, and communication. The data were collected by questionnaire and analyzed by a multiple multilevel logistic regression run on Stata 13.Results: Bullying increased depression (b= 3.69; 95% CI= 1.51 to 9.00; p= 0.004) and poor communication (b= 4.95; 95% CI= 2.24 to 10.89; p <0.001). Bullying decreased academic achievement (b= - 5.68; 95% CI= -12.33 to -2.62; p<0.001). School had strong contextual effect on depression with ICC= ICC= 20.91%.Conclusion: Bullying increases depression and poor communication. Bullying decreases academic achievement. School has strong contextual effect on depression.Keywords: bullying, depression, Health Belief Model, Social Cognitive TheoryCorrespondence: Kiyat Sudrajad. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36 A, Surakarta, 57126, Central Java. Email: kiyatrambo@gmail.com. Mobile: +6285647116834.Journal of Health Promotion and Behavior (2020), 05(02): 79-86https://doi.org/10.26911/thejhpb.2020.05.02.02